Appraisal of the Sesame production opportunities and constraints, and farmer-preferred varieties and traits, in eastern and southwestern Ethiopia - Teklu, D.H.; Shimelis, Hussein; Abebe, A.T.; Abady, S. (MDPI, 2021)
Sesame (Sesamum indicum L.) is an important oilseed crop with well-developed value chains. It is Ethiopia’s most valuable export commodity after coffee (Coffea arabica L.), contributing to socioeconomic development. The productivity of the crop is low and stagnant in Ethiopia and other major sesame growing regions in sub-Saharan Africa (<0.6 t/ha) due to a multitude of production constraints. The objective of this study was to document sesame production opportunities and constraints, as well as farmer- and market-preferred varieties and traits, in eastern and southwestern Ethiopia as a guide for large-scale production and breeding. A participatory rural appraisal (PRA) study was conducted in two selected sesame growing regions and four districts in Ethiopia. Data were collected from 160 and 46 sesame farmers through semistructured questionnaires and focus group discussions. Sesame is grown by all respondent farmers in the study areas for food and as a source of cash. Most respondent farmers (56%) reported cultivating sesame using seeds of unknown varieties often sourced from the informal seed sector. About 83% of the respondents reported lack of access to improved seeds as the most important production constraint, followed by low yield gains from cultivating the existing varieties (reported by 73.8% of respondents), diseases (69.4%), and low market price (68.8%). Other production constraints included insect pests (59.4%), lack of market information (55%), and high cost of seed (50%). The above constraints were attributed to the absence of a dedicated breeding programme, lack of a formal seed sector, poor extension services, and underdeveloped pre- and postharvest infrastructures. The most important market-preferred traits of sesame included true-to-type seed (reported by 36.3% of respondents), white seed colour (28.8%), and high seed oil content (23.8%). The vital farmer-preferred attributes included reasonable market price (reported by 11.3% of respondents), resistance to crop diseases (10.9%), drought tolerance (10.3%), resistance to crop insect pests (9.2%), higher seed yield (8.9%), higher thousand-seed weight (7.2%), higher oil content (6.3%), white seed colour (6.1%), early maturity (6.1%), and good oil qualities such as aroma and taste (5.7%). Therefore, there is a need for a dedicated sesame genetic improvement programme by integrating the above key production constraints and market- and farmer-preferred traits to develop and deploy new generation varieties to enhance the production, productivity, and adoption of sesame cultivars in Ethiopia.